Gender Trends in Obstetrics and Gynecology Department-Based Leadership Roles Across American College of Obstetricians and Gynecologists Districts [121]. (May 2015) - Aluko, Ashley; Hofler, Lisa Gay; Hacker, Michele R.; Dodge, Laura E.; Ricciotti, Hope A.
Abstract : INTRODUCTION: We aimed to determine whether the gender of department-based leaders in American College of Obstetricians and Gynecologists (College) districts reflects the composition of the obstetrics and gynecology physician base. METHODS: We searched U.S. obstetrics and gynecology departmental web sites for the gender of leaders (chairs, vice chairs, division directors, clerkship directors, residency directors, and fellowship directors). The proportion of female obstetrician–gynecologists (ob-gyns) in each College district was derived from 2013 Association of American Medical Colleges data. We compared proportions of female leaders and female ob-gyns within each district and calculated ratios of the proportions (1.0 indicates proportional representation of female leaders). RESULTS: A total of 50.2% of active ob-gyns were women. In each district the proportion of female leaders was lower than the proportion of female ob-gyns; this discrepancy was statistically significant for all districts (all P <.03) except VIII (Northwest, Southwest, West), IX (California), and XII (Florida). The ratio of female leaders to ob-gyns was above 0.80 in Districts VI (Midwest), VIII, and IX but below 0.60 in District III (Mid-Atlantic) and VII (South). The ratio was below 0.80 for the chair role in all districts, with a low of 0.15 in District XI (Texas). The ratio was above 0.80 for the clerkship director role in all districts and residency director in all but three districts. CONCLUSION: There was notable geographic variation in representation of women in department-based leadership roles relative to gender composition of the physician base. The proportion of female leaders was lower than the proportion of female ob-gyns in every district. Women were more often underrepresented in administrative than educational roles.